2020
DOI: 10.1111/aogs.13886
|View full text |Cite
|
Sign up to set email alerts
|

Detection of copy number variants with chromosomal microarray in 10 377 pregnancies at a single laboratory

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Wapner et al enrolled 4406 women and demonstrated an increased diagnostic rate in microarray over karyotyping of 6.0% among cases with ultrasound abnormalities and 1.7% among pregnant women with advanced maternal age or positive screening results [ 33 ]. A 2020 study indicated that the frequency of pathogenic or likely pathogenic CNVs is 1.2% in all indications by prenatal SNP array [ 34 ]. A recent review summarized a total of 29,612 cases using array techniques in foetuses with abnormal structures and the rate of pathogenic or likely pathogenic CNVs was 0.4–2.5% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wapner et al enrolled 4406 women and demonstrated an increased diagnostic rate in microarray over karyotyping of 6.0% among cases with ultrasound abnormalities and 1.7% among pregnant women with advanced maternal age or positive screening results [ 33 ]. A 2020 study indicated that the frequency of pathogenic or likely pathogenic CNVs is 1.2% in all indications by prenatal SNP array [ 34 ]. A recent review summarized a total of 29,612 cases using array techniques in foetuses with abnormal structures and the rate of pathogenic or likely pathogenic CNVs was 0.4–2.5% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Their detection, especially in prenatal diagnosis where fetal anomalies are identified, is vital for clinical decision-making and parental counseling. [3][4][5] Chromosomal microarray (CMA) has long been considered the gold standard for identifying CNVs and is widely accepted as the first tier diagnostic tool in cases of congenital anomalies Additionally, the use of single nucleotide polymorphism (SNP) arrays provides valuable genotyping information which enables the detection of copy number neutral absence of heterozygosity (AOH), which may arise from a deletion, autozygosity (identity-by-descent), or certain types of uniparental disomy (UPD)-isodisomy. However, with advancements in NGS technology, it is prudent to recognize the limitations of microarray technology and consider the benefits of NGS.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormalities including Copy Number Variants (CNVs) are a well‐recognized cause of human disease, many of which are present in prenatal and neonatal periods as fetal structural anomalies and congenital malformations 1–3 . Their detection, especially in prenatal diagnosis where fetal anomalies are identified, is vital for clinical decision‐making and parental counseling 3–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the yield of pCNV was 6%-7% in ultrasonography anomalous fetuses with a normal karyotype, 7,8 and 0.4%-2% in fetuses without anomalies. [9][10][11] Cardiovascular, genitourinary, skeletal, and central nervous system defects were reported to be most commonly associated with chromosomal aberrations. [12][13][14][15][16][17][18] Therefore, the American College of Obstetricians and Gynecologists (ACOG) and the Society for Maternal-Fetal Medicine (SMFM) recommend CMA as a first-tier test in the diagnostic evaluation of fetal structural abnormalities for fetuses undergoing prenatal diagnosis.…”
Section: Introductionmentioning
confidence: 99%